Da escola ao des-emprego: A educação profissional Brasileira em questão - Stênico, Joselaine Andréia de Godoy [UNESP]; Adam, Joyce Mary [UNESP] (My University, 2016)
The paper analyzes the Brazilian Professional Education, investigating if the professional education favors the insertion of the young in the labor market. The research took a qualitative approach, guided by the collection and analysis of data from large national form of bases it is possible to draw conclusions based on literature. Among the results, it is noteworthy that although the professional education the purpose of developing skills for a productive life, in practice this does not occur, the data indicate that there is a lag between what is proposed and what actually occurs, pointing to serious education inefficiency indexes.
From school to un-employment: The Brazilian professional education in question
Keywords: Education and Manpower; Professional Education; Qualification; Skill